Strategi Pendidikan Solat Bagi Anak Dalam Perspektif Islam Dan Psikologi Perkembangan - Witjoro, Wisnu Adi; Megi Andika (STAI Bumi Silampari, 2025)
The five daily prayers are the mahdhah worship which is the pillar of the Islamic religion. Apart from being a form of devotion to Allah SWT, prayer also has a deep spiritual dimension. Through prayer, a Muslim can communicate directly with Allah, ask for forgiveness, and achieve peace of mind. Prayer also functions as a means to cleanse the heart of despicable traits and instill noble moral values. Psychologically, prayer can have a positive effect on mental health, such as reducing stress and increasing feelings of optimism. The five daily prayers not only have an individual dimension, but also a social dimension. When Muslims gather in the mosque to perform congregational prayers, they build ukhuwah Islamiyah and strengthen ties of brotherhood. Prayer is also a means of fostering a sense of solidarity and concern for others. In the context of a pluralistic society, prayer can become the identity and unification of Muslims. The history of the five daily prayers has long and deep roots. The command to pray was first given to the Prophet Muhammad SAW in Hira Cave. Since then, prayer has become a very important act of worship in Islam. Throughout history, prayer has undergone various developments and adaptations, but its essence and purpose remain the same, namely as a form of self-servation to Allah SWT. In the context of modern life, the implementation of the five daily prayers is often faced with various challenges, such as busy work, lifestyle demands, and foreign cultural influences. Therefore, it is important to continue to explore the meaning and values ??of prayer and look for ways to perform prayer better in the midst of modernity.